2022
DOI: 10.1212/nxi.0000000000200012
|View full text |Cite
|
Sign up to set email alerts
|

AMPA Receptor Encephalitis in a Patient With Metastatic Breast Cancer Receiving Palbociclib

Abstract: ObjectiveTo report a case of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor encephalitis (AMPARE) as a potential immune-mediated complication of palbociclib (a cyclin-dependent kinase 4/6 inhibitor).BackgroundMedication-induced autoimmune encephalitis is an increasingly recognized entity. To date, cases have been reported with immune checkpoint inhibitors (ICIs), typically within 3 months and while cancer is responding to immunotherapy.ResultsA 55-year-old woman with metastatic breast cancer pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In summary, DPPX antibody-mediated encephalitis is a rare condition with atypical symptoms, often leading to potential misdiagnoses as cerebrovascular disease or other systemic disorders. Other autoimmune antibodies secondary to breast cancer such as AMPAR antibodies [ 21 ] and RI antibodies [ 22 ] have also been reported, which should be considered to make an accurate clinical diagnosis. At the same time, previous studies have only found that DPPX antibody-mediated AE is related to lymphoma, and others can not be seen.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, DPPX antibody-mediated encephalitis is a rare condition with atypical symptoms, often leading to potential misdiagnoses as cerebrovascular disease or other systemic disorders. Other autoimmune antibodies secondary to breast cancer such as AMPAR antibodies [ 21 ] and RI antibodies [ 22 ] have also been reported, which should be considered to make an accurate clinical diagnosis. At the same time, previous studies have only found that DPPX antibody-mediated AE is related to lymphoma, and others can not be seen.…”
Section: Discussionmentioning
confidence: 99%